2022
DOI: 10.5534/wjmh.210175
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Testosterone on Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease responsible for almost half of all dementia cases in the world and progressively increasing. The etiopathology includes heritability, genetic factors, aging, nutrition, but sex hormones play a relevant role. Animal models demonstrated that testosterone (T) exerted a neuroprotective effect reducing the production of amyloid-beta (Aβ), improving synaptic signaling, and counteracting neuronal death. This study aims to evaluate the impact of T deprivation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 120 publications
(169 reference statements)
0
21
0
Order By: Relevance
“…Conversely, in a smaller study involving 296 older men by Schneider et al, testosterone has been shown to increase the risk of panic and phobic anxiety in patients with a genetically determined long CAG repeat polymorphism of the androgen receptor [ 137 ]. Regarding the effects of androgens in the elderly, it has been reported that low testosterone serum levels are independently associated with incident dementia and Alzheimer’s disease, confirmed by an increased incidence of those conditions in ADT patients [ 147 , 148 ]. Conversely, further evidence is required to enlighten the relation between testosterone and Parkinson’s disease, considering the neuroprotective effects of 5-alfa reductase inhibitors in animal models [ 149 ].…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Conversely, in a smaller study involving 296 older men by Schneider et al, testosterone has been shown to increase the risk of panic and phobic anxiety in patients with a genetically determined long CAG repeat polymorphism of the androgen receptor [ 137 ]. Regarding the effects of androgens in the elderly, it has been reported that low testosterone serum levels are independently associated with incident dementia and Alzheimer’s disease, confirmed by an increased incidence of those conditions in ADT patients [ 147 , 148 ]. Conversely, further evidence is required to enlighten the relation between testosterone and Parkinson’s disease, considering the neuroprotective effects of 5-alfa reductase inhibitors in animal models [ 149 ].…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Pathologies or symptoms related to AD usually occur before and/or concomitantly with the onset of symptoms, such as memory loss. Multiple factors are associated with AD, including hypertension, diabetes, hypercholesterolemia, obesity, and depression [ 1 ], as well as sex hormones [ 11 ] and hyperhomocysteinemia [ 12 ], all of them linked in some way to Cu and S disturbances.…”
Section: Linking Ad Predisposing Factors To Cu and S Metabolismmentioning
confidence: 99%
“…For instance, androgen deprivation therapy (ADT) is known to increase the risk of bone fracture [ 26 ], diabetes [ 27 , 28 ], and cardiovascular disease [ 29 , 30 ], although there are some ways to mitigate these concerns [ 31 ]. Since testosterone has a neuro-protective effect including the improvement of energy metabolism and reduction of oxidative stress in neurons [ 32 ], ADT may deteriorate cognitive function [ 33 ] and may increase the risk of dementia as well [ 34 ]. Low serum testosterone level also correlates positively with lean body mass, which can be calculated by subtracting the weight of all the fat from the total weight of the body [ 35 ].…”
Section: Surgical Tolerability In ‘Elderly’ Patientsmentioning
confidence: 99%